Interval and Ratio Scaling of Spectral Audio Descriptors - Kazazis, Savvas; Depalle, Philippe; McAdams, Stephen (Frontiers in Psychology, 2022)
Two experiments were conducted for the derivation of psychophysical scales of the following audio descriptors: spectral centroid, spectral spread, spectral skewness, odd-to-even harmonic ratio, spectral deviation, and spectral slope. The stimulus sets of each audio descriptor were synthesized and (wherever possible) independently controlled through appropriate synthesis techniques. Partition scaling methods were used in both experiments, and the scales were constructed by fitting well-behaving functions to the listeners’ ratings. In the first experiment, the listeners’ task was the estimation of the relative differences between successive levels of a particular audio descriptor. The median values of listeners’ ratings increased with increasing feature values, which confirmed listeners’ abilities to estimate intervals. However, there was a large variability in the reliability of the derived interval scales depending on the stimulus spacing in each trial. In the second experiment, listeners had control over the stimulus values and were asked to divide the presented range of values into perceptually equal intervals, which provides a ratio scale. For every descriptor, the reliability of the derived ratio scales was excellent. With the exception of spectral centroid, for which the zero point of the scale was assigned empirically, the rest of the scales were assigned a zero point that also has a physical meaning. The unit of a particular scale was assigned empirically as well, so as to facilitate comparisons between the derived perceptual ratio scales of all audio descriptors. The construction of psychophysical scales based on univariate stimuli allowed for the establishment of cause-and-effect relations between audio descriptors and perceptual dimensions, contrary to past research that has relied on multivariate stimuli and has only examined the correlations between the two.